PERSEPSI PEGAWAI KANTOR URUSAN AGAMA (KUA) KECAMATAN BALIKPAPAN TIMUR TENTANG BIMBINGAN PRA NIKAH - Faishol, Imam; Thohiroh, Nafisatun (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
Pre-marital guidance has become a regulation of the Ministry of Religion. With the aim of providing an understanding of domestic life in realizing a sakinah mawaddah wa rahmah family, and can minimize the occurrence of disputes, violence and even divorce. Bride and groom in East Balikpapan sub-district participated in a pre-wedding guidance program for initial debriefing for prospective brides at KUA provided by BP4 (Marriage Advisory, Guidance, and Preservation Agency). Through this program, the prospective bride and groom will be required to attend pre-wedding classes or guidance for approximately 16 hours of meetings to obtain a certificate which will later be used as a requirement when carrying out a marriage at the KUA. The KUA employee of East Balikpapan District agrees with the existence of pre-marital guidance. That way the bride and groom get education for their readiness, regardless of the assumption that people who are getting married do not need to take part in these activities. However, the optimality of pre-wedding guidance carried out at the KUA of East Balikpapan District is only like a supplement, sufficient but not optimal, in the implementation of pre-wedding debriefing there are still many shortcomings, such as short time and the material provided is also lacking in depth.